2023
DOI: 10.1021/acs.inorgchem.3c00616
|View full text |Cite
|
Sign up to set email alerts
|

2D Cu(I)-I Coordination Polymer with Smart Optoelectronic Properties and Photocatalytic Activity as a Versatile Multifunctional Material

María Murillo,
Reinhold Wannemacher,
Juan Cabanillas-González
et al.

Abstract: This work presents two isostructural Cu­(I)-I 2-fluoropyrazine (Fpyz) luminescent and semiconducting 2D coordination polymers (CPs). Hydrothermal synthesis allows the growth of P-1 space group single crystals, whereas solvent-free synthesis produces polycrystals. Via recrystallization in acetonitrile, P21 space group single crystals are obtained. Both show a reversible luminescent response to temperature and pressure. Structure determination by single-crystal X-ray diffraction at 200 and 100 K allows us to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Pilar Amo-Ochoa et al reported that [Cu 2 I 2 (Fpyz)] n and [Cu(Cl-HIN)I] n CPs having Cu 2 I 2 chains present better conductivity ( σ ∼ 10 −5 S cm −1 ) than CP1 due to shorter Cu–I distances. 70,71 Some previously reported Cu( i ) CPs, having a Cu 2 I 2 double chain, similar to CP1 , have been reported to show electrical conductivity in a similar range. 65,72–75 A comparison of the electrical conductivities of CP1 with some previously reported CPs bearing a Cu 2 I 2 core is presented in Table S8 (ESI†), suggesting comparable values for CP1 .…”
Section: Resultsmentioning
confidence: 85%
“…Pilar Amo-Ochoa et al reported that [Cu 2 I 2 (Fpyz)] n and [Cu(Cl-HIN)I] n CPs having Cu 2 I 2 chains present better conductivity ( σ ∼ 10 −5 S cm −1 ) than CP1 due to shorter Cu–I distances. 70,71 Some previously reported Cu( i ) CPs, having a Cu 2 I 2 double chain, similar to CP1 , have been reported to show electrical conductivity in a similar range. 65,72–75 A comparison of the electrical conductivities of CP1 with some previously reported CPs bearing a Cu 2 I 2 core is presented in Table S8 (ESI†), suggesting comparable values for CP1 .…”
Section: Resultsmentioning
confidence: 85%
“…Adsorption and chemical and biological oxidation are some techniques that have been used to remove organic dyes from water. However, these methods are costly as well as time-consuming. , To develop sustainable material/catalyst for dye degradation, one must consider cost-effectiveness, design, market viability, technology, and environmental impact of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Copper iodide (CuI) hybrid materials have attracted much attention and have been extensively explored in the past decade, thanks to their applications in different fields of material science. The charge-neutral inorganic motif Cu n I n can take many different forms. CuI 1D chains, Cu 2 I 2 rhomboid dimers, and Cu 4 I 4 cubane tetramers are the most common secondary building units (SBUs), leading to the formation of zero-dimensional (0D) discrete clusters to one-dimensional (1D) extended chains, two-dimensional (2D) sheets, and three-dimensional (3D) networks. Apart from the rich structural diversity, less toxicity, cost-effectiveness, unique luminescence, and semiconducting properties further increase the applicability of these hybrid materials. …”
Section: Introductionmentioning
confidence: 99%